Thomas Watt Gregory papers - Gregory, Thomas Watt, 1861-1933.
Correspondence, memoranda, printed copies of speeches and writings, legal briefs, pleadings, and other papers relating to Gregory's service as U.S. attorney general and to his law practice in Washington, D.C., and Houston, Texas. Subjects include the Woodrow Wilson presidential administration; arming of merchant ships and procedures for dealing with enemy aliens during World War I; the Industrial Conference held in Washington, D.C., 1919-1920; and Franklin D. Roosevelt's presidential campaign of 1932. Other subjects include Texas state politics, the University of Texas, Ku Klux Klan, and Stone Mountain Confederate Monumental Association. Includes legal case files pertaining to wartime seizure of the property of aliens, claims against Mexico, boundary disputes between Texas and Oklahoma, stockholders' suits against railroads, corporate tax and contract involving oil companies and railroads, and the settlement of estates.
Correspondents include George Weston Anderson, Newton Diehl Baker, Ray Stannard Baker, Bernard M. Baruch, R.L. Batts, Louis Dembitz Brandeis, William Jennings Bryan, Albert Sidney Burleson, Carrie Chapman Catt, Tom Connally, Josephus Daniels, John W. Davis, John Nance Garner, William Hitz, Herbert Hoover, Edward Mandell House, Louis M. Howe, Robert Lansing, Thomas R. Marshall, Earle Bradford Mayfield, W.G. McAdoo, James Clark McReynolds, William D. Mitchell, Daniel James Moody, A. Mitchell Palmer, Key Pittman, Franklin D. Roosevelt, Charles Seymour, Morris Sheppard, George Carroll Todd, Willis Van Devanter, Thomas James Walsh, Edward Douglass White, George W. Wickersham, Edith Bolling Galt Wilson, and Woodrow Wilson.
U.S. attorney general, regent of the University of Texas, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Card index to the correspondence available in the Library of Congress Manuscript Reading Room.
Keywords: Anderson, George Weston, -- 1861-1938 -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Batts, R. L. -- 1864-1935 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Burleson, Albert Sidney, -- 1863-1937 -- Correspondence; Catt, Carrie Chapman, -- 1859-1947 -- Correspondence; Connally, Tom, -- 1877-1963 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Davis, John W. -- 1873-1955 -- Correspondence; Garner, John Nance, -- 1868-1967 -- Correspondence; Hitz, William, -- 1872-1935 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Howe, Louis M. -- 1871-1936 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Marshall, Thomas R. -- 1854-1925 -- Correspondence; Mayfield, Earle Bradford, -- 1881-1964 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; McReynolds, James Clark, -- 1862-1946 -- Correspondence; Mitchell, William D. -- 1874- -- Correspondence; Moody, Daniel James, -- 1893-1966 -- Correspondence; Palmer, A. Mitchell -- 1872-1936 -- Correspondence; Pittman, Key, -- 1872-1940 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Seymour, Charles, -- 1885-1963 -- Correspondence; Sheppard, Morris, -- 1875-1941 -- Correspondence; Todd, George Carroll, -- 1879- -- Correspondence; Van Devanter, Willis, -- 1859-1941 -- Correspondence; Walsh, Thomas James, -- 1859-1933 -- Correspondence; White, Edward Douglass, -- 1845-1921 -- Correspondence; Wickersham, George W. -- 1858-1936 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; United States. -- Department of Justice. -- Office of the Attorney General; Ku Klux Klan (19th cent.); Stone Mountain Confederate Monumental Association; University of Texas; Alien property -- United States; Aliens -- United States; Arbitration, Industrial -- United States; Executors and administrators; Labor -- United States; Memorials -- Georgia; Merchant marine -- United States; Petroleum industry and trade; Practice of law -- Texas -- Houston; Practice of law -- Washington (D.C.); Presidents -- United States -- Election -- 1932.; Railroads; Stone Mountain Memorial (Ga.); World War, 1914-1918.; World War, 1914-1918 -- Naval operations; Oklahoma -- Boundaries -- Texas; Texas -- Boundaries -- Oklahoma; Texas -- Politics and government